Postcommunist Citizens in an Integrated Europe - Stanisław Konopacki (Journal of Social Science Education, 2013)
The main aim of this paper is to demonstrate the limits of European citizenship and European collective identity in the context of the latest enlargements of the EU, i.e. the accession of postcommunist countries of Central and Eastern Europe in 2004 and 2007. The introduction of transitional periods for the free movement of persons with regard to the ‘new European citizens’, as well as the deportation of Roma from France in 2010, demonstrate that something is amiss with the concept of EU citizenship and the ‘European identity’ which would permit such practices. It is a fear of the Other as an essential element of European identity. The paper concludes by drawing on the work of Emmanuel Levinas and Jacques Derrida, examing the prospects that they open up for thinking differently about European identity.